In search of the active chlorine species on Ti/ZrO2-RuO2-Sb2O3 anodes using DEMS and XPS. (10th June 2018) - Palma-Goyes, R.E.; Vazquez-Arenas, J.; Ostos, C.; Manzo-Robledo, A.; Romero-Ibarra, I.; Calderón, J.A.; González, I.
Abstract: Evidence to what it is identified in the literature as "active chlorine" in indirect oxidation processes occurring on Ti/ZrO2 -RuO2 -Sb2 O3 anodes is provided in this study. To discriminate such behavior, different catalysts are prepared using the Pechini method varying ZrO2 content, at different Zr/Ru molar ratios: 1, 0.5 and 0.3. The characterization of the materials using X-ray photoelectron spectroscopy (XPS) reveals that no solid solution (Ru-Zr) or any doping that affects the crystalline phase of Zr are obtained, while Sb2 O3 was surface-segregated from the bulk to the anode surface affecting the outmost 3–5 nm surface layers. There are enormous impacts on the catalytic activity and adsorption properties of the structures as ZrO2 content is increased. The presence of ZrO2 and Sb2 O3 shrink the number of favorable oxygen adsorption sites in Ti/ZrO2 -RuO2 -Sb2 O3 catalysts, whence the adsorption energies for oxygen-metal interactions became lower than for Ti/RuO2 . Differential electrochemical mass spectroscopy (DEMS) and electrochemical experiments qualitatively indicate that a lower amount of ZrO2 in the ternary electrode induce a better catalysis towards the oxygen evolution reaction (OER, O2 production), while the ionic currents for C l O − and H C l O species drop. This behavior suggests that chloride oxidation needs to encompass the mitigation of the OER as the percentage of ZrO2 is increased in the anode. Active chlorine could stem from H C l O a d s species since it was produced in larger amounts than C l O a d s − according to the pH of the electrolyte, and in adequate levels to generate the degradation of organic compounds. Graphical abstract: Highlights: Impacts on the catalytic activity and adsorption properties due to ZrO2 . Adsorption energies for O2 -metal interactions became lower due to ZrO2 and Sb2 O3 . Active chlorine could stem from HOClads according to the electrolyte pH. Chloride oxidation involves the inhibition of the oxygen evolution reaction. A higher amount of ZrO2 in Ru-Zr material catalyzes the active chlorine production.